2023
DOI: 10.19206/ce-170267
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on selected physical properties of diesel–ethanol–dodecanol blends

Artur Krzemiński,
Artur Jaworski,
Hubert Kuszewski
et al.

Abstract: The article presents findings of the comparative analyses of the selected physicochemical parameters of diesel fuel and diesel-ethanol blends with addition of dodecanol, used in order to stabilise the blend Diesel fuel and the blends were tested for density, flash point and cold filter plugging point. The physicochemical propertis were assessed in seven samples with different proportional volume of ethanol contained in diesel fuel. Homogeneous blends were produced by adding 5% dodecanol to blends containining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The basic parameters of the fuel blends, defined based on the authors' own measurements, are shown in Table 5. The related methodology has been reported in other publications [14,41]. The basic parameters of the fuel blends, defined based on the authors' own measurements, are shown in Table 5.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The basic parameters of the fuel blends, defined based on the authors' own measurements, are shown in Table 5. The related methodology has been reported in other publications [14,41]. The basic parameters of the fuel blends, defined based on the authors' own measurements, are shown in Table 5.…”
mentioning
confidence: 99%
“…The basic parameters of the fuel blends, defined based on the authors' own measurements, are shown in Table 5. The related methodology has been reported in other publications [14,41].…”
mentioning
confidence: 99%